Secretarial work in the Covid-19 pandemic: the perception of professionals regarding the adaptation to remote work on the pandemic context: the perception of professionals regarding the adaptation to remote work on the pandemic context - Brandão, Yasmim Francyne; Franklin, Luiza Amalia Soares; Zuin, Debora Carneiro (Revista Expectativa, 2025)
This study's main objective was to investigate the perception of executive secretaries regarding the adaptation of remote work during the Covid-19 pandemic. To this end, the concept and regulation of teleworking was analyzed, in addition to its benefits, difficulties and the secretarial skills involved. Using online forms and semi-structured interviews, a qualitative and descriptive research was carried out with ten graduated executive secretary professionals and working in different organizations. It was found that most of them felt prepared, totally or in part, to continue their activities working from home, thus demonstrating the ability to adapt. Among the challenges of this pandemic period, the internal communication of organizations was especially evident, which was affected due to the isolation and, consequently, the distance from co-workers. However, most participants mentioned communication competence as being very important when it comes to teleworking. It was also observed that challenges existed, however, they didn’t prevent the demands from being carried out and fulfilled. Finally, most of the interviewees identified benefits and positive points through the experience of remote work, whether in their personal life or for the organizations as a whole.